Non‐Hodgkin lymphoma in Southern Africa: review of 487 cases from The International Non‐Hodgkin Lymphoma Classification Project. (21st December 2015) - Perry, Anamarija M.; Perner, Yvonne; Diebold, Jacques; Nathwani, Bharat N.; MacLennan, Kenneth A.; Müller‐Hermelink, Hans K.; Bast, Martin; Boilesen, Eugene; Armitage, James O.; Weisenburger, Dennis D.
Summary: Comparative data on the distribution of non‐Hodgkin lymphoma (NHL) subtypes in Southern Africa (SAF) is scarce. In this study, five expert haematopathologists classified 487 consecutive cases of NHL from SAF using the World Health Organization classification, and compared the results to North America (NA) and Western Europe (WEU). Southern Africa had a significantly lower proportion of low‐grade (LG) B‐NHL (34·3%) and a higher proportion of high‐grade (HG) B‐NHL (51·5%) compared to WEU (54·5% and 36·4%) and NA (56·1% and 34·3%). High‐grade Burkitt‐like lymphoma was significantly more common in SAF (8·2%) than in WEU (2·4%) and NA (2·5%), most likely due to human immunodeficiency virus infection. When SAF patients were divided by race, whites had a significantly higher frequency of LG B‐NHL (60·4%) and a lower frequency of HG B‐NHL (32·7%) compared to blacks (22·5% and 62·6%), whereas the other races were intermediate. Whites and other races had a significantly higher frequency of follicular lymphoma and a lower frequency of Burkitt‐like lymphoma compared to blacks. The median ages of whites with LG B‐NHL, HG B‐NHL and T‐NHL (64, 56 and 67 years) were significantly higher than those of blacks (55, 41 and 34 years). Epidemiological studies are needed to better understand these differences.